Lighting the participatory spark? The role of social media influencers in initiating political participation - Reinikainen Hanna; Borchers Nils S.; Suuronen Aleksi; Strandberg Kim (Nordicom Review)
The role of social media influencers is often limited to the realm of consumer behaviour. However, recently, their role in the sphere of political communication has become a new topic of interest. In this article, we focus on how political influencer content is perceived by Finnish social media users and probe the interrelations between these perceptions and political participation. A moderated mediation model was developed and tested using data gathered from Finnish respondents (n = 680) through an online survey and self-reported measures. The results imply that perceived exposure to political influencer content is associated with latent political participation (i.e., increased attention and awareness), which is further related to manifest political participation (e.g., boycotting and voting). The moderating effects of general political interest and engagement with influencers were also tested, but not found. The findings suggest that influencers’ political content has the potential to spark political participation, as it may ignite awareness towards political topics – possibly even among those who have not previously shown interest in politics. Suchawareness, in turn, may eventually manifest itself as political behaviour, such as voting or boycotting. The results provide an enhanced understanding of the potential impact of new social media arenas on increasing political participation while simultaneously contributing to the studies on political influencers, a research area that is growing in popularity.